2014
DOI: 10.1080/14786419.2014.984181
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme mediated-transesterification of verbascoside and evaluation of antifungal activity of synthesised compounds

Abstract: Enzymatic acylation of verbascoside, a polyhydroxylated natural product, has been reported in this study using five different commercial lipases and taking p-nitrophenyl alkanoates as acyl donors. Out of these enzymes, the immobilised Candida antarctica lipase B was found as the enzyme of choice. Mono-and diacylated products were formed, with mono as major product indicating high regioselective nature of such transformations. A series of acyl esters of verbascoside have been synthesised by this enzymatic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Oyourou et al (2013) has confirmed the in-vivo antifungal activity of verbascoside (I07) from Lantana camara leaves, where they suggested its potential use as an alternative fungicide in agriculture against Penicillium digitatum infections. The synergistic antifungal activity of some verbascoside (I07) acyl esters derivatives and amphotericin B against C. albicans has been studied, and up to a four-fold reduction in the MIC was demonstrated (Khazir et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Oyourou et al (2013) has confirmed the in-vivo antifungal activity of verbascoside (I07) from Lantana camara leaves, where they suggested its potential use as an alternative fungicide in agriculture against Penicillium digitatum infections. The synergistic antifungal activity of some verbascoside (I07) acyl esters derivatives and amphotericin B against C. albicans has been studied, and up to a four-fold reduction in the MIC was demonstrated (Khazir et al, 2015).…”
Section: Discussionmentioning
confidence: 99%